Social Deixis Composition In English And Uzbekistan - Rajabboqiyeva, Barno (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article analyzes the cognitive-semantic features of social deixis in English and Uzbek. Social deixis plays a key role in expressing social relations, respect, and intimacy through linguistic means in communication. The study provides a comparative analysis of forms of address, titles, honorifics, and markers of politeness in English and Uzbek, highlighting how they reflect social status and conversational context. From the perspective of cognitive semantics, the research explores the conceptual domains, meanings, and cultural factors shaping these linguistic units.